2001
DOI: 10.1128/jvi.75.6.2566-2574.2001
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Localization and Shuttling of Herpes Simplex Virus Tegument Protein VP13/14

Abstract: The herpes simplex virus type 1 gene UL47 encodes the tegument proteins referred to collectively as VP13/14, which are believed to be differentially modified forms of the same protein. Here we show that the major product of the UL47 gene during transient expression is VP14, suggesting that some feature of virus infection is required to produce VP13. We have tagged VP13/14 with green fluorescent protein and have demonstrated that the protein is targeted efficiently to the nucleus, where it often localizes in nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 55 publications
5
68
0
Order By: Relevance
“…In COS-7 cells transfected with pCIgC and pCIgD, the glycoproteins gC and gD had a membranous localisation similar to that reported in bovine cells [14,37,47]. VP8 had a nuclear localisation that was also consistent with the previously reported localisation of VP8 in BoHV-1 infected cells [53] and the reported localisation of the homolog protein VP13/14 of HSV-1 in transfected mammalian cells [12]. As expected, truncated forms of the glycoproteins gC and gD localised in the secretory pathways and were found in the supernatant of transfected cells.…”
Section: Discussionsupporting
confidence: 85%
“…In COS-7 cells transfected with pCIgC and pCIgD, the glycoproteins gC and gD had a membranous localisation similar to that reported in bovine cells [14,37,47]. VP8 had a nuclear localisation that was also consistent with the previously reported localisation of VP8 in BoHV-1 infected cells [53] and the reported localisation of the homolog protein VP13/14 of HSV-1 in transfected mammalian cells [12]. As expected, truncated forms of the glycoproteins gC and gD localised in the secretory pathways and were found in the supernatant of transfected cells.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies of HSV-1 have suggested that both UL46 and UL47 have a role in enhancing UL48-induced immediate-early viral gene expression (19,40,41). Nuclear localization has been demonstrated for UL47 (8,30), supporting a role in regulation of UL48 activity. Using green fluorescent protein fusion proteins, UL46 was only found in the cytoplasm (38), arguing against a role for regulation of UL48 activity in the whole cell.…”
Section: Discussionmentioning
confidence: 99%
“…RNA and shuttles between the cytoplasm and the nucleus (28). In injunction with ICP27, U L 47 binds and displaces PABC1 from the poly(A) binding protein complex at the cap structure (29).…”
Section: Significancementioning
confidence: 99%